Longer-term safety and tolerability of canagliflozin in patients with type 2 diabetes: a pooled analysis. (4th March 2017) - Qiu, Rong; Balis, Dainius; Xie, John; Davies, Michael J.; Desai, Mehul; Meininger, Gary
Abstract: Objective: To evaluate the longer-term safety of canagliflozin, a sodium glucose co-transporter 2 (SGLT2) inhibitor, in patients with type 2 diabetes mellitus (T2DM). Methods: The safety/tolerability of canagliflozin 100 and 300 mg were assessed using data pooled from seven placebo- and active-controlled studies of 52–104 weeks in duration that enrolled a broad range of patients with T2DM ( N = 5598). Canagliflozin 100 and 300 mg as monotherapy or in combination with various background antihyperglycemic agents (AHAs) were compared with pooled non-canagliflozin treatments (i.e. placebo, sitagliptin, glimepiride). Safety was assessed based on adverse event (AE) reports, including the incidence of AEs related to the mechanism of SGLT2 inhibition. Results: Overall AE incidence was similar with canagliflozin 100 and 300 mg and non-canagliflozin (73.7%, 74.5%, and 73.7%). The incidence of AE-related discontinuations and serious AEs was low and balanced across groups. The incidence of male and female genital mycotic infections, urinary tract infections, and AEs related to osmotic diuresis or volume depletion was higher with canagliflozin versus non-canagliflozin; these AEs generally occurred early with decreased incidence over time and incidence was similar across baseline HbA1c subgroups. The incidence of fractures and diabetic ketoacidosis was low and similar across groups. Canagliflozin was associated with a low incidence of hypoglycemia when used with background AHAs that are not associated with hypoglycemia; the incidence was higher among patients on background AHAs associated with hypoglycemia (i.e. insulin, sulfonylurea, glinide). Limitations: Limitations of this analysis include its post hoc nature. While this analysis included a broad population of patients, including those with a history or risk of cardiovascular disease or chronic kidney disease, the longer-term safety in these patient populations was not specifically evaluated. Ongoing outcome studies will provide data on the long-term safety of canagliflozin in these populations. Conclusions: Longer-term exposure to canagliflozin as monotherapy or in combination with other agents was generally well tolerated in patients with T2DM. Trial registration: ClinicalTrials.gov identifiers: NCT01106625, NCT01081834, NCT01106677, NCT00968812, NCT01106651, NCT01106690, NCT01137812.